Larvosio; where I briefly tell my experience as a "Larva"’s corrector and I make other considerations - Hermosilla, Alejandro (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The article is based on my particular experience as a Larva’s corrector. A novel similar to a living being and different from most of the books as it causes anomalous readings and interpretations as I have been able to experience during my work. Larva always tells us, points out, suggests something new and different. It is a novel doomed to it. It doesn’t matter how many times you read it. In this article I will delve into what has been my relationship with the novel as a corrector.